California Italian studies - University of California (System). Italian Studies Multicampus Research Group; California Digital Library. eScholarship (EScholarship, University of California, 2010)
The California Italian Studies Journal is a digital, peer-reviewed, open access journal committed to publishing innovative and influential scholarly work in the field of Italian Studies. The nascent journal will feature interdisciplinary, comparative, and critical scholarship.
Keywords: Italian literature : History and criticism : Periodicals; Civilization; Italian literature; Italy : Civilization : Periodicals; Italy : History : Periodicals; Italy; Italy